ความคิดเห็นของบุคลากรกรมสุขภาพจิตต่อกิจกรรมการฟื้นฟูสมรรถภาพทางจิตเวช - รวินันท์ ทองขาว (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
Background: Psychiatric health problem reported by World Health Organization about 450 million people. Psychiatric rehabilitation is a crucial strategy in prevention of chronic illness and recurrent of diseases, which was estimated 42.6% of mental disorders. Therefore, opinions of health personnel in Mental Health Department toward psychiatric rehabilitation activities were an important information to improve service quality. Objectives: To study opinion of health personnel in Mental Health Department toward specified psychiatric rehabilitation activities. Research Design: Cross-sectional descriptive study. Study population: Health personnel in Mental Health Department such as doctors, pharmacists, nurses, social workers and other personnel. Sample size: Personnel in 4 psychiatric hospital, 682 from 916 persons (response rate 74.5%) Statistic: Unpaired t-test, Paired t-test, One-way ANOVA and Wilcoxon Signed-Ranks test. Research tools: Self-administered questionnaire. Results: Health personnel respondents were female (78.0%), mean age 39.3 years, undergraduate education (72.2%), health worker level (81.4%), mean psychiatric work experience 16.1 years. From 28 activities listed in 5 dimensions, the important and real amount of practice were rated by the respondents. The results showed that all of the activity importance were rated higher mean scores than those activities of real practice. The social dimensions of psychiatric rehabilitation activities, the importance and real practice were marked as highest means scores (4.11 and 3.10). Moreover, more than 50% of the respondents, rated 22 out of 28 activities as very high important activities (score 4+5) and the first 3 rank were as follow: self-care skills, living skills and working skills, however, only 3 out of 28 activities of the real amount of practice were marked as very high scores by more than 50% and those 3 specified were self-care skills, living skills and leisure skills. For activities provision for relatives, more than 50% of respondents marked the important activities with higher scores than the real practice in all activities. Furthermore, age group, level of education, present job position, experiences training, orientation and psychiatric hospital location affect the differences in opinion statistically significant (p< 0.05). The top-3 obstacles, were stated as follow: lack of knowledge, capabilities or skills and co-ordination of work system. Conclusion: From this research, psychiatric rehabilitation activities which respondents marked high score should be considered as key performance indicators in the future standard guideline for psychiatric rehabilitation practice. The reasons of no activity or low activity amount of practice marked might be inadequate training experiences, Mental Health Department should support in training to improve the efficiency of psychiatric rehabilitation.